Human Adaptation to Coastal Hazards in Greater Bridgetown, Barbados - Mycoo, Michelle; Robinson, Stacy-Ann; Nguyen, Cindy; Nisbet, Catherine; Tonkel, Rock (Frontiers in Environmental Science, 2021)
As urban risks associated with a changing climate continue to intensify, it is increasingly important to broaden our understanding of climate vulnerabilities in coastal cities and human adaptation to climate-related hazards. Coastal cities in small island developing states in the Caribbean stand to be among the most climate-impacted. This paper explores vulnerability to coastal hazards (sea-level rise, storm surges and flooding) in Barbados’ capital city and its urban corridor – Greater Bridgetown. The research is underpinned by three questions: (1) In what ways is Greater Bridgetown vulnerable to coastal hazards? (2) What are the human dimensions of this vulnerability? and (3) What are the associated human adaptations? We apply a four-component adaptive urban governance framework to explore the role of the city’s historical development, urban morphology, national-level institutions and relevant government and other stakeholder initiatives in shaping, reducing and/or increasing vulnerability to coastal hazards. In totality, a case is presented that highlights Greater Bridgetown’s capacity for coastal/urban resilience, but which cannot be maximized without institutional prioritization of vulnerability, increased stakeholder “buy-in” and participation, along with significant investment in adaptation and the protection of valuable coastal infrastructure. The findings are of relevance to human adaptation within coastal cities of small island developing states.